PENGARUH KADAR TIMBAL DALAM DARAH TERHADAP LAJU ENDAP1DARAH PADA1IBU HAMIL DI1DAERAH PANTAI KABUPATEN1BREBES - Muhammad Sulthan Mubarok; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Low hemoglobin in pregnant women will cause health problems. Lead can inhibit synthetic heme pathway so that it can affect the sedimentation rate The average lead level in pregnant women was 19.74 + 9.417 μg / dL which had exceeded the normal limit (5 μg / dL).. This study aimed to determine the correlation between blood lead level and erythrocyte sedimentation rate in pregnant women in the coastal district of Brebes. This type of research was an analytic observational study with cross sectional approach. The population in this study were all pregnant women in the working area of Puskesmas Wanasari, Puskesmas Kluwut, Puskesmas Bulakamba, Puskesmas Tanjung, Puskesmas Kecipir, and Puskesmas Losari 1734 people. Samples used as many as 98 pregnant women used purposive sampling technique. The result of the study by Spearman rank correlation test showed that there was no correlation between the levels of lead in the blood and erythrocyte sedimentation rate in 1 hour (p = 0,198; r = 0,123) even to the erythrocyte sedimentation rate in 2 hours (p = 0,292; r = 1,00). The conclusion that the majority of pregnant women who have blood levels above normal also have above normal blood sedimentation rates.